A pesquisa e a prática docente: investigação sobre hipóteses que alunos de 5ª série formulam a respeito de escritas algébricas - Oliveira, Ieda Mara (2005)
In this current work of the course of Professional Master of Mathematical Education paper, entitled "Investigations on hypotheses that students formulate about algebraic writings , we emphasize our concern with the teaching and learning of Algebra, which is always very present in our practice and that led us to look for researches developed about this theme and also historical studies on the development of Algebra, whose knowledge is very needed in the formation of a teacher of Mathematics. We present the results of an investigation performed with my fifth-grade students, in which we tried to identify the hypotheses that they formulate about the use of letters. We conclude, by trying to establish a relationship between the performance of this research and our professional development and also emphasizing the relevance of this research, in the scope of the teacher's work, related to the construction of a quotidian attitude in the search for the comprehension of their students' learning and development processes and to the autonomy in the interpretation of reality and the knowledge that constitutes their teaching objects. We also consider fundamental the knowledge by the teacher, of investigation methods used in the development of researches in Mathematical Education with emphasis on those which focus on the knowledge, the experience, the formation and the professional development as a tesacher